Fishery resources in Brazil: technological appropriation for sustainable development. - Nascimento, Glória Cristina Cornélio do; Córdula, Eduardo Beltrão de Lucena; Benício, Danniely Alves; Oliveira, Patrícia Aguiar de; Silva, Maria Cristina Basílio Crispim da (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
This study aimed to analyze the main sustainable technologies in the fishery sector of Brazil, given that, the global demand for fish as foodhas grown rapidly, due to the population increase, and the search for healthier foods. The technological appropriation in this area can be seen as a milestone in overcoming the environmental problems which have occurred for decades, due to the uncontrolled exploitation of natural resources. This analysis was performed through the literature in national journals, aiming at the search for technological innovations in the various modalities of fish and crustacean breeding. In the field of pisciculture, there was the development of technologies to accelerate fish growth and fattening, especially concerning the type of management, genetics, feed, and other techniques that have been adopted around the world, and also in Brazil. In shrimp farming, the reuse of water in the tanks has been considered a clean and sustainable practice. Therefore, the technological appropriation contributes positively to the management of fishery resources, in order to provide techniques and consistent domains with environmental conservation and sustainable farming practices, increasing the production and reducing environmental impacts throughits sustainable perspective.